2011
DOI: 10.1016/j.acthis.2009.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apolipoprotein M in human hepatocellular carcinoma tissues

Abstract: SummaryThe present study examined mRNA levels and protein mass of apolipoprotein M (apoM) in human hepatocellular carcinoma (HCC) tissues and in its adjacent tissues. Plasma apoM levels in these HCC patients were also determined and compared to the normal subjects. The mean level of plasma apoM in the HCC patients was 0.61±0.30 OD*mm -2 , which was significantly higher than that in the normal subjects 0.37±0.07 OD*mm -2 (P<0.01). However, both apoM mRNA levels and apoM protein mass in the HCC tissues were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Indeed, the key finding of our study was a significant positive correlation in vivo between serum apoM and HBV DNA levels in HBeAg-negative patients. These results are consistent with and extend previous findings that CHB patients exhibit elevated serum apoM levels [11, 12]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, the key finding of our study was a significant positive correlation in vivo between serum apoM and HBV DNA levels in HBeAg-negative patients. These results are consistent with and extend previous findings that CHB patients exhibit elevated serum apoM levels [11, 12]. …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that chronic hepatitis patients exhibit higher serum apoM levels than healthy control subjects [11, 12]. Similarly, HepG2 cells transfected with an infectious HBV clone were found to express significantly higher levels of apoM mRNA and protein than uninfected HepG2 cells in vitro.…”
Section: Introductionmentioning
confidence: 84%
“…It has been reported that the plasma apoM levels were higher in the patients suffered from HCC and other chronic liver diseases than in normal subjects[28,29]. Our result is in line with earlier results from experiment based on semiquantitatively determined by both dot-blotting and western blotting analysis[29]. However, we didn't find any correlation between HBV viral load and ApoM levels.…”
Section: Discussionsupporting
confidence: 91%
“…Recent observations strongly suggest that apoM is predominantly confined to the HDL particles in human plasma and it may have antiatherogenic properties involving in the conversion of large HDL to pre-β HDL, the later mainly functions as an acceptor of peripherally deposited cholesterol that is described as the revise cholesterol transportation [9,17]. Moreover other researches indicated that apoM might be also involved in the immunity, inflammation, and neoplasia [18-20]. However, the physio-pathological functions of apoM are still not fully revealed.…”
Section: Discussionmentioning
confidence: 99%